Effects of verapamil and nifedipine on carrageenan-induced inflammation in the rat paw - M Khaksari; M.A Sajadi (Journal of Kerman University of Medical Sciences, 1999)
the extracardiac actions of calcium-channel belockers has little been studied.in fact,it has been demonstrated in a number of in viro studies,that calcium-channel belockers are involved in inflammation.here,we evaluated the dose-dependent Effects of verapamil and nifedipine on carrageenan-induced, acute inflammation in the rat paw compared to the anti-inflammatory activites of ibuprofen.the adult male rats were divided into two groups.paw edema was induced by intraplantar injection of 0.1 ml of 0.5% carrageenan solution.different doses of infedipine(10,25,100,200,mg/kg) and verapamil(25,100,400,mg/lg) and ibuprofen 12 mg/lg given intrapritoneally after carrageenan injection.assessment of edema performed by calculation of volume changes and by extravasation of evans blue in test grop compared to the control,one hour after injection of carrageen.verapamil and infedipine showed significantly inhibitory effect on increased edema.maximum inhibition(83+_10%) were induced by infedipine at 100mg/kg and verapamil at 25mg/kg.nifedipine inhibited  paw edema in a dose-dependent manner.the inflammation was significantly reduced(37+_5.2%) by infedipine at 200mg/lg,whereas verapamil did not have any effect.Ibuprofen reduced increased volume of paw and evans blue content by 83+_11.5% and 42+_6.3% respectively.no signifigant differences were found between inhibitory effects of nifedipine and ibuprofen.according to this results,calcium-channel blockers can inhibit acute flammatory responses in the paw,and these effects are comparable to ibuoprpfen.